Top 3: Pension Systems in Denmark, Finland, and the Netherlands - Svend E. Hougaard Jensen; Jukka Lassila; Niku Määttänen; Tarmo Valkonen; Ed Westerhout (The Research Institute of the Finnish Economy (ETLA), 2019)
According to the 2018 Mercer Global Pension index, the pension systems of Denmark, Finland and the Netherlands are the best three in the world. This paper seeks to identify the common elements of success of these three pension systems, including the institutional framework within which they operate. We emphasize the collective and compulsory nature of the earnings-related pension schemes and the important role for social partners in all three pension systems. We also discuss what we believe are the most important challenges these systems face.
Keywords: D58; E21; H55; H68; J11; J26; 330; Pensions; Pension taxation; Fiscal sustainability; Saving; Retirement